2019
DOI: 10.1037/hea0000712
|View full text |Cite
|
Sign up to set email alerts
|

Promoting physical activity among cancer survivors: Meta-analysis and meta-CART analysis of randomized controlled trials.

Abstract: Promoting physical activity among cancer survivors: meta analysis and metacart analysis of randomized controlled trials Article (Accepted Version) (2019) Promoting physical activity among cancer survivors: meta-analysis and meta-cart analysis of randomized controlled trials. Health Psychology.We thank Jennifer Walker and Rachael Posey (Medical Librarians) for invaluable assistance with the computerized literature searches. AbstractObjective: We conducted a meta-analysis of physical activity interventions amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 182 publications
1
35
1
Order By: Relevance
“…Patients may underestimate how the treatment might affect their ability to exercise on their own. Also, current evidence indicates that exercise under supervision yields better outcomes . Therefore, even for currently active patients, regular evaluation of activity levels is needed, and referral to exercise programming could be valuable.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 99%
See 3 more Smart Citations
“…Patients may underestimate how the treatment might affect their ability to exercise on their own. Also, current evidence indicates that exercise under supervision yields better outcomes . Therefore, even for currently active patients, regular evaluation of activity levels is needed, and referral to exercise programming could be valuable.…”
Section: What Oncology Clinicians Can Do Now: Assess Advise and Refermentioning
confidence: 99%
“…A meta‐analysis of 14 randomized controlled trials among breast cancer survivors found that, although large effects on physical activity were reported by programs that provided more supervision, interventions by telephone or email were also effective . A recent comprehensive review of interventions for cancer survivors across different approaches, samples, and settings (128 randomized controlled trials, for a total of 13,050 patients with cancer) revealed that supervised programs produced larger effects on physical activity than unsupervised programs . Another review concluded that interventions that have used behavioral theory tend produce the largest overall effect size for behavior change .…”
Section: Behavioral Considerations and Patient Preferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…For the moderation analyses examining hypothetical purchases by warning topic, we used 2 effect sizes from Ang et al [41], 1 for health warning versus control and 1 for nutrient warning versus control. For these 2 effect sizes, we partitioned the control group sample size equally across the 2 treatment arms, following others [42,43]. This approach partially (but not completely) corrects for correlation among effect sizes, so this moderation analysis should be interpreted with caution [43].…”
Section: Quantitative Synthesis and Meta-analysismentioning
confidence: 99%